Evolução espaço-temporal da ocupação urbana sobre áreas naturais no município de Natal-RN - Costa, Joseane Dunga da (2015)
In this work the landscape morphodynamics was used to check the strength and importance of the changes carried out by man on the environment over time, in Natal-RN municipality. The occupation of partially preserved natural areas was analyzed, but environmentally fragile, such as riparian forests, vegetation on the banks of waterways, which play regulatory role of the water flow, and the dunes, which guarantee the rapid recharge of aquifers. The impacts of urban sprawl in Natal Southern and West zones Were identified and characterized, through a detailed mapping in the period between 1969 and 2013 the main Permanent Preservation Areas - PPA (banks of rivers and lagoons, and dunes remaining) and their temporal changes. For this were used aerial photographs and satellite imagery, altimetry data, and pre-existing information, which allowed the creation of a spatial database, and evolution of maps of impervious areas, evolution of the use and occupation and Digital Terrain Model (DTM) from contour lines with contour interval of 1 meter. Based on this study presents a diagnosis of the environmental situation and the state of conservation of natural areas, over the last 44 years, compared to human pressures. In general, it was found that the urban settlement has advanced about 60% of studied natural areas. This advance was growing by the year 2006, when there was a slowdown in the process, except for the Environmental Protection Zone (EPZ) 03, where the river Pitimbú and your PPA, which experienced a more significant loss area. The urban occupation affected the natural drainage and contributed to the contamination of groundwater Natal, due to increased sealed area, the release of liquid and solid waste, as well as the removal of riparian vegetation. Changed irreversibly the natural landscape, and reduced the quality and quantity of water resources necessary for the population. Thus, it is necessary to stimulate the adoption of use and protection of PPA planning measures, to the preservation of the San Valley Region inserted into the EPZ 01, and integrate more remaining dunes, in good condition, this EPZ, due to the importance of those remaining on the environment and the maintenance of quality of life. It is suggested, also, protection of catchment areas, such as PPA ponds and Pitimbú River. Finally, it is expected that this study can assist the managers in making decisions in urban and environmental planning of the municipality